The role of KIR and HLA interactions in pregnancy complications - Colucci, Francesco (Immunogenetics (New York), 2017)
Combinations of KIR and HLA genes associate with pregnancy complications as well as with many other clinical scenarios. Understanding how certain KIR and HLA genes influence the biology of a disease is, however, a formidable challenge. These are the two most variable gene families in the human genome. Moreover, the biology of a disease is best understood by studying the cells of the affected tissue. Natural Killer (NK) cells express KIR and are the most abundant leukocytes in the uterus. Most of our knowledge of NK cells is based on what we have learned from cells isolated from blood, but these are different from their tissue resident counterparts, including uterine NK (uNK) cells. Reproductive immunology faces an additional challenge: Two genotypes must be considered because both maternal and foetal HLA class I molecules may influence the outcome of pregnancy, most likely through interactions with maternal KIR expressed on uNK cells. Maternal uNK cells are not spontaneously cytotoxic and instead engage in interactions with trophoblast. We hypothesise that these interactions regulate allocation of resources between the foetus and the mother and may go wrong in diseases of pregnancy.